2008
DOI: 10.1021/jo801668b
|View full text |Cite
|
Sign up to set email alerts
|

Dicobalt Hexacarbonyl Complexes of Alkynyl Imines in a Sequential Staudinger/Pauson−Khand Process. A Route to New Fused Tricyclic β-Lactams

Abstract: Dicobalt hexacarbonyl complexes of alkynyl imines were allowed to react with ketenes via Staudinger reaction. Sequential [2 + 2] cycloaddition/Pauson-Khand reaction led to structurally new fused-tricyclic beta-lactams and fused-azabicyclic cyclopentenones. Chemoselectivity, scope, and limitation of the process were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Recently, Bertrand and coworkers reported that hexacarbonyldicobalt complexes of alkynyl imines could be used for a sequential Staudinger/Pauson–Khand process to generate a variety of structurally novel fused tricyclic β‐lactams (Scheme ) 117…”
Section: Tandem Reactions and Selected Applications Of Carbonylatimentioning
confidence: 99%
“…Recently, Bertrand and coworkers reported that hexacarbonyldicobalt complexes of alkynyl imines could be used for a sequential Staudinger/Pauson–Khand process to generate a variety of structurally novel fused tricyclic β‐lactams (Scheme ) 117…”
Section: Tandem Reactions and Selected Applications Of Carbonylatimentioning
confidence: 99%
“…Firstly, Bertrand reported the combination of a Staudinger reaction with a PKR for the synthesis of bi-and tricyclic azetidinone products (Scheme 72). 252 The reaction sequence proceeds via the formation of a propargylic imine, which undergoes a Staudinger reaction with the in situ generated ketene and a final PKR leads to the tricyclic product 133 which is formed in up to 53% yield.…”
Section: Scheme 71mentioning
confidence: 99%
“…The most common approach to access such chemotype is the Pauson-Khand (PK) reaction [39,40], consisting of a [2 + 2 + 1] cycloaddition between an olefin, alkyne, and carbon monoxide. This reaction has been also applied in cascade approaches [41], and in combination with RCM [42], Diels-Alder [43] and Staudinger [44] reactions to produce novel structurally complex chemical entities. Following our interest to DOS as a synthetic strategy for the generation of molecular scaffolds according to a couple/pair approach [45][46][47], we reasoned to combine the copper-catalyzed ketone-amine-alkyne (KA 2 ) multicomponent coupling reaction [48] with the Pauson-Khand cycloaddition as the pairing reaction to achieve spirocyclic pyrrolocyclopentenone derivatives.…”
Section: Introductionmentioning
confidence: 99%